ANALISIS PERATAAN LABA (INCOME SMOOTHING) : Faktor-Faktor yang Mernpengaruhi dan Kaitannya dengan Kinerja Saham Perusahaan Publik di Indonesia - Harry Prihatmoko; Wibowo Wibowo; Murtanto Murtanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
The objective of research is to analysis any factors which its influencing to income smoothing and its correlation to stock performance (return and risk) of public companies in Indonesia.Data of this research were obtained from 30 companies listed in Jakarta Stock Exchange which have been selected using (purposive) judgment sampling method. Samples were classified to be smoother and non smootherusing Eckel's model (1981). Eckel model classification in this research use three object of variable of income : operation income, income before tax, and income after tax. Test of One-Sample Kolmogmv Smimov, Mann-Whitney, t-Test, and Mult4variate Logistics were used for data analysing.The result of this research indicate that the coefficient variation of operating income and income before tax shows that: company size, net profit margin (NPM), industrial sector, and winnernosser stocks are not influencing income smoothing. Based on coefficient of variation of income after tax indicates that company size, net profit margin (NPM), and industrial sector are not influencing income smoothing while winner/losser stocks influence income smoothing. And it also indicated that there are not difference return between smoother and non smoother. The risk also is not different between them.Keywords: income smoothing, return, risk,